Ovarian vein thrombosis: Incidence of recurrent venous thromboembolism and survival - Wysokinska, Ewa M.; Hodge, David; McBane, Robert D., II (Thrombosis and Haemostasis, 2006)
For patients with ovarian vein thrombosis (OVT), neither the rate of recurrence nor the expected survival are well established. Clarification of these natural history data would aid in defining the optimal management. We studied all female patients with OVT seen at the Mayo Clinic between 1990 and 2006. Survival, recurrent venous thrombosis rates, and prothrombotic factors were compared to a randomly selected group of 114 female patients with lower extremity venous thrombosis (DVT). Patients with OVT (n=35; mean age 44.8 ± 17.9 years) were significantly more likely to be under hormonal stimulation (48%), have an underlying malignancy (34%), experienced recent pelvic infection (23%) or undergone recent surgery (20%), compared to DVT patients. Duringa mean follow-up period of 34.6 ± 44.3 months, three patients suffered three recurrent venous thrombi (event rate: three per 100 patient years of follow-up).This recurrence rate was comparable to patients with lower extremity DVT (2.2 per 100 patient years). Recurrent thrombosis involved the contralateral ovarian vein, left renal vein, and inferior vena cava. The five-year mortality rate for OVT patients was 43% compared to 20% for DVT patients (p=0.08). All OVT deaths were cancer related. Survival was greater in OVT patients without cancer compared to those with active cancer (p<0.0001). In conclusion, venous thromboembolism recurrence rates are low and comparable to lower extremity DVT. Therefore general treatment guidelines for lower extremity DVT may be applicable. Poor survival rates in OVT are principally governed by the presence of malignancy.
Keywords: Ovarian vein; venous thrombosis; hormones